PROFESIONALITAS GURU AKIDAH AKHLAK DALAM MENINGKATKAN PEMBENTUKAN KARAKTER SISWA DI MADRASAH ALIYAH NURUL IMAN ULU GEDONG KOTA JAMBI - Juanda; Hasanah, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the professionalism of Aqidah Akhlak teachers in improving the character formation of eleventh-grade male students at Madrasah Aliyah Nurul Iman, Ulu Gedong, Jambi City. The study focuses on three main aspects: teachers’ efforts in strengthening students’ character, supporting and inhibiting factors affecting teacher professionalism, and the key aspects of teacher professionalism in shaping students’ character. This research employed a descriptive qualitative approach. Data were collected through interviews, classroom observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. To ensure the trustworthiness of the findings, triangulation was applied to meet the criteria of credibility, transferability, dependability, and confirmability. The results show that teachers improve students’ character through advice, exemplary behavior, and the habituation of positive values in daily school activities. Supporting factors include teachers’ educational background and teaching experience, collaboration among teachers and school members, and a supportive school environment. Meanwhile, the main inhibiting factors are limited instructional time and negative peer influences. Furthermore, teacher professionalism is reflected in four core competencies, namely pedagogical, personal, social, and professional competencies, which collectively contribute to the development of students’ discipline, responsibility, and moral conduct.